Efficacy of S-1 in colorectal cancer. (August 2014) - Miyamoto, Yuji; Sakamoto, Yasuo; Yoshida, Naoya; Baba, Hideo
<x xml:space="preserve">Abstract</x> Introduction: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=S-1&logicalOpe1=OR&field2=articletitle&text2=S-1&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">S-1 is an oral fluoropyrimidine that consists of tegafur, 5-chloro-2, 4-dihydroxypyridine and potassium oxonate. It has been developed as a prodrug of 5-fluorouracil with the goal of improving therapeutic efficacy and tolerability. Areas covered: This review aims to provide an evidence-based update of clinical trials that have investigated the clinical efficacy, adverse-event profile, dosage and administration of S-1, given alone or in combination with conventional chemotherapeutics and new target-oriented drugs, in the management of colorectal cancer (CRC). Additionally, differences in the tolerability and pharmacokinetics of S-1 between Caucasians and Asians have been described. Finally, the therapeutic efficacy of S-1 regarding metastatic CRC or postoperative CRC has been discussed. Available data have stimulated further research, including Phase III trials for the treatment of advanced CRC. Expert opinion: Treatment using S-1 combined with oxaliplatin (± bevacizumab) and irinotecan has achieved promising results in terms of feasibility, safety and effectiveness. Furthermore, S-1 is an acceptable treatment as adjuvant chemotherapy for colon cancer.